The blurred image - Lucendo Lacal, Santiago (Re-visiones, 2024)
In 1989, an exhibition of a large selection of photographs with blurs, or even blurry photographs, was presented in Vanishing Presence, at the Walker Art Center in Minneapolis. The exhibition established the trajectory of the blur, ranging from the effects produced by technical inability to its subsequent use as an intentional resource [4]. These ’defects’, like ghostly apparitions, continue to manifest, perhaps even more so, in the digital era. The present article attempts to address this type of fuzzy images (digital and analogical), their evocative and significant capacity, as well as to emphasize the power of the Gothic imagery (in the broadest sense) to represent the terrors of the present and the future.